Inovação nos serviços de hotelaria hospitalar: um estudo em dois hospitais de Porto Alegre - Sanz, José Antônio Barroso (Universidade do Vale do Rio dos Sinos, 2010)
The ascension of the services' sector in the national economy follows a world-wide trend. Allied to this growth, the practical innovators that start to be used by companies of services represent essential ingredients in the underling of competitive advantages. Moreover, existing innovations in some sector are transferred to other sectors, adding bigger value to activities and services. For example, the introduction of hotel concepts to hospital environment brings attendance's alternatives to patients and theirs family. The aim of this work is to describe and analyze which innovations in services are appearing as result from the introduction of hotel practices in the hospitals. The research is based on two case studies. Public and private hospitals had been analyzed, both located in the city of Porto Alegre - RS and representing distinct forms of management system. The choice of those hospitals was given, mainly, for the presence of an internal hotel management, responsible for controlling all activities from hotel sector. Interviews had been conducted in person and also through email, with professionals from the medical area as much as the hotel sector of the two hospitals, in order to identify which would be these innovations. During data collection, in addition to interviews, participant observation was carried out in both hospitals, thus enhancing the analysis presented during the interviews. From the analytical categories created and the data collection, some conclusions could be observed, such as: i) the hotel managements of the hospitals are still incipient, not getting a lot of autonomy in decision-making, ii) the innovations are usually perceived services based on ad hoc approaches (interaction between provider and client), iii) a hospital hotel is still synonymous with support health services, iv) the hotel practices become more pleasant hospital environments, and may qualify the service rendered the client.
Keywords: Inovação; Serviços; Hotelaria hospitalar; Hospitalidade; Innovation; Services; Hospital hospitality; Hospitality; ACCNPQ::Ciências Sociais Aplicadas::Administração